Development of a bioassay reagent using Photobacterium phosphoreum as a test for the detection of aquatic toxicants - Ronco, Alicia Estela (1992)
Lyophilized cells of Photobacterium phosphoreum, rehydrated in 2% (w/v) NaCl in 0.022M KH₂PO₄ at pH 7.0, were used for developing an assay to test the acute toxicity of organic and inorganic compounds. The standardized assay gave good reproducibility of results with 11 organic and four inorganic compounds. Results were compared with reported data obtained with other test organisms and are within their sensitivity ranges. Environmental screening of wastes from oil and petrochemical industries is discussed.